Caracterização dos processos de eletrodo em compostos do tipo LixNiyCo1-yO2 utilizando técnicas de impedância - Marchesi, Luís Fernando Quintino Pereira (Universidade Federal de São Carlos, 2005)
In this work a qualitative study was carried out, using electrochemical impedance spectroscopy (EIS), exchanging cobalt by nickel in LixNiyCo1-yO2 compound synthetized by method of the polymeric precursor (Pechini s Method). A systematic study of LixCoO2 compound was also carried out to, used as cathode material in rechargeable lithium ion batteries. In this systematic study of LixCoO2 the structural characterization was made, by x-ray diffraction, and the identification of different possible structures was made by the structural refinement (Rietveld s Method), being based on three possible structures: LixCoO2 (layered), LiCo2O4 and Co3O4 (both spinel-type). The LixCoO2 electrodes were electrochemically characterized by cyclical voltammetry, to study the system s reversibility, chronopotenciometry, to study the system specific capacity, and electrochemical impedance spectroscopy, to understanding chemical and physical system s phenomena. The LixCoO2 compounds had layered-type structure like the main phase, showed by Rietveld s Method. To the same oxide, cyclical voltammetry showed reversible processes of oxidation/reduction. Chronopotenciometry showed a lost in specific capacity caused by increase of spinel-type structure. The add of nickel on compound became easier the oxidation/reduction process, although this was carried out by the increase of the spinel-type structure to.
Characterization of the processes in electrode of LixNiyCo1-yO2 compounds using impedance techiniques
Keywords: Eletroquímica; Impedância eletroquímica; Eletrodos; Óxidos metálicos; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA